Ireland : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This report discusses the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Ireland. The report provides a summary of the AML/CFT measures in place in Ireland as at July 2005, analyzes those measures, and provides recommendations on how certain aspects of the system could be strengthened. It also sets out Ireland's levels of compliance with the FATF 40 Recommendations.